2021
DOI: 10.5114/ada.2021.108435
|View full text |Cite
|
Sign up to set email alerts
|

Assessing quality of life in patients with mastocytosis: development of the disease-specific questionnaire

Abstract: Introduction: Appropriate and targeted psychological care, as well as psychoeducation covering the disease causes, symptoms, and their management are crucial elements of the therapeutic process in patients with mastocytosis. This care is based on the identification of problematic areas that are of the greatest importance for patients. The quality of life questionnaires available in Poland are designed for the general population; therefore, they do not encompass the specificity of difficulties experienced by pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…It has been previously reported that 42.4% of mastocytosis patients experienced a psychological burden and a mild life impairment level 50 . However, many authors have recommended more detailed and personalized psychological interviews to complement the assessment 51 . It is important to note that different depression diagnostic criteria and cutoffs were used in the different studies included in this review.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been previously reported that 42.4% of mastocytosis patients experienced a psychological burden and a mild life impairment level 50 . However, many authors have recommended more detailed and personalized psychological interviews to complement the assessment 51 . It is important to note that different depression diagnostic criteria and cutoffs were used in the different studies included in this review.…”
Section: Discussionmentioning
confidence: 99%
“… 50 However, many authors have recommended more detailed and personalized psychological interviews to complement the assessment. 51 It is important to note that different depression diagnostic criteria and cutoffs were used in the different studies included in this review. For instance, studies employing the Hamilton‐17 scale considered scores >8 as indicative of mild depression, >17 as moderate and >24 as severe.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, most of these existing PBMs were developed decades ago. Perceptions on important aspects of HRQoL may change over time [ 9 , 35 , 36 ], which motivated, in part, the recent development of new instruments, both generic and disease specific, in Western countries [ 17 , 20 , 37 , 38 ]. Compared with existing generic PBMs, a unique item in the CHROME-G is appetite.…”
Section: Discussionmentioning
confidence: 99%